O poder na aldeia. - Vendrame, Maíra Ines, author.
1 online resource (xiv, 243 pages)
Keywords: "This book explores the formation of Italian rural society in southern Brazil from the late nineteenth century through an examination of how Italian peasants in northern Italy and southern Brazil solved issues related to family honor. Looking at social networks and justice practices, it offers an understanding of the restoration of social balance in these communities, and explores the culture of immigrants. It will be of interest to scholars working in Italian history, Brazilian history, immigration history and the history of colonialism. It will also be of interest to scholars working on ethnographic and religious history, as well as to social anthropologists."--